Axisymmetric free vibration of layered cylindrical shell filled with fluid - Izyan, Nurul Mat Daud; Sabri, Nur Ain Ayunni; Hafizah, A. K. Nor; Sankar, D.S.; Viswanathan, K.K. (Zielona Góra: Uniwersytet Zielonogórski)
The aim of the study is to analyse the axisymmetric free vibration of layered cylindrical shells filled with a quiescent fluid. The fluid is assumed to be incompressible and inviscid. The equations of axisymmetric vibrations of layered cylindrical shell filled with fluid, on the longitudinal and transverse displacement components are obtained using Love`s first approximation theory.
Keywords: axisymmetric; free vibrations; cylindrical shells; Love`s first approximation theory; inviscid fluid; spline approximation; eigenvalues